REDEFENISI KONSEP PERKAWINAN ISLAM DI INDONESIA (Kompromi Pemikiran Islam Progresif dengan Ijtihad Ibn Hazm) - Imran, Maizul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
Renewal of Islamic thought could not be done, if the hesitant and stiff attitude of thinking still exist on the scholars and Muslims. In contrast, progressive and dynamic attitude is very important, but caution remains a necessity. Moreover, reformation efforts demanded the authorities to be open minded in creating new law and freely performing istinbath and istidlÄl in representing the substantive meaning of syara'. Studies on the progressive dimension of Islam is now starting to promoted flarely with two basic consciousness: 1) as a positive response to the world pressures that seen Islam as a religion that always slow respond to the pace of the times so that there are very strong boundary between the Islamic world and the western world. 2) as a strategy to fight extreme thoughts which always blamed on Islam with the empowerment of progressive elements in the Muslim community and bridge the gap between the Islamic world and the western world. These two things become the urgency of scientific study and progressive dissemination of Islam. Ibn Hazm (4th century H) thought which is textual turned out to provide great opportunities and high motivation to carry the issues of modernity. Despite a lot of criticism and negative judge of Ibn Hazm ijtihad because of the political, social and culture influence in his time, some even claim that fiqh ZhÄhiriyyah often can not adapt to the times. it was found the thought that can be compromised to meet the needs of modernity in an effort to redefine the concept of Islamic marriage in Indonesia.